# Reasoning Questions (Inequality) for LIC AAO/IBPS SO Exams

Reasoning Questions (Inequality) for LIC AAO/IBPS SO Exams Set-23:
Dear Readers, Important Practice Reasoning Questions for Upcoming AAO/SO Exams was given here with Explanations. Aspirants those who are preparing for the examination can use this.

Directions (1โ10): In these questions, relationship between different elements is shown in the statements. The statements are followed by conclusions. Study the conclusions based on the given statements and select the appropriate answer:

1). Statements:         L = P โค W< V โค K โฅ Q; B< L; K = M
Conclusions:             I. B< V           II. M> P
a)    Only conclusion I is true
b)    Only conclusion II is true
c)    Either conclusion I or II is true
d)    Both conclusion I and II are true
e)    Neither conclusion I nor II is true

2). Statements:         L = P โค W< V โค K โฅ Q; B< L; K = M
Conclusions:             I, L> Q            II. W = M
a)    Either conclusion I or II is true
b)    Neither conclusion I nor II is true
c)    Only conclusion I is true
d)    Only conclusion II is true
e)    Both conclusion I and II are true

3). Statements:         R โค U = B< S; B โค X
Conclusions:             I. X> R          II. X = R
a)    Both conclusion I and II are true
b)    Either conclusion I or II is true
c)    Only conclusion I is true
d)    Neither conclusion I nor II is true
e)    Only conclusion II is true

4). Statements:         C> U โค S< T = O> D โฅ Y; Z = O โค P
Conclusions:             I. U> D           II. S< P
a)    Neither conclusion I nor II is true
b)    Both conclusion I and II are true
c)    Only conclusion I is true
d)    Either conclusion I or II is true
e)    Only conclusion II is true

5). Statements:         C> U โค S< T = O> D โฅ Y; Z = O โค P
Conclusions:             I. Z> Y            II. C< O
a)    Only conclusion I is true
b)    Both conclusion I and II are true
c)    Only conclusion II is true
d)    Either conclusion I or II is true
e)    Neither conclusion I nor II is true

6). Statements:         P = N โฅ Q> R, K< T = R
Conclusions:             I. P> K                       II. Q> T
a)    Only conclusion I is true
b)    Only conclusion II is true
c)    Either conclusion I or II is true
d)    Neither conclusion I nor II is true
e)    Both conclusion I and II are true

7). Statements:         G< W = S โค H, Z โฅ B = G
Conclusions:             I. W< Z           II. H> B
a)    Only conclusion I is true
b)    Only conclusion II is true
c)    Either conclusion I or II is true
d)    Neither conclusion I nor II is true
e)    Both conclusion I and II are true

8). Statements:         C โฅ D โฅ N = J< K โค R
Conclusions:             I. R> N           II. D โฅ K
a)    Only conclusion I is true
b)    Only conclusion II is true
c)    Either conclusion I or II is true
d)    Neither conclusion I nor II is true
e)    Both conclusion I and II are true

9). Statements:         E โฅ G> H< I, K = M โฅ N< E
Conclusions:             I. M = G           II. N โฅ H
a)    Only conclusion I is true
b)    Only conclusion II is true
c)    Either conclusion I or II is true
d)    Neither conclusion I nor II is true
e)    Both conclusion I and II are true

10). Statements:      L โค M> N โฅ R, G> S= T โฅ R
Conclusions:             I. T โค N           II. G> R
a)    Only conclusion I is true
b)    Only conclusion II is true
c)    Either conclusion I or II is true
d)    Neither conclusion I nor II is true
e)    Both conclusion I and II are true

1). d) 2). b) 3). b) 4). e) 5). a) 6). e) 7). b) 8). a) 9). d) 10). b)

Solution:

1). Given statements:
L = P โค W< V โค K โฅ Q         โฆ.(i)
B< L                                      โฆ(ii)
K = M                                     โฆ(iii)
Combining (i) and (ii), we get
B< L   = P โค W< V โค K โฅ Q
Thus, B< V is true. Hence I is true.
Again, combining (i) and (iii), we get
L = P โค W< V โค K = M
Thus, P< M or M> P is true. Hence conclusion II is true.

2). Given statements:
L = P โค W< V โค K โฅ Q         โฆ.(i)
B< L                                      โฆ(ii)
K = M                                     โฆ(iii)
Combining (i) and (iii), we get
B< L   = P โค W< V โค K = M
Thus, W< M is true. Hence II (W = M) is not true.
Again, from (i), L = P โค W< V โค K โฅ Q
We canโt compare L and Q. Hence I (L> Q) is not true

3). Given statements:
R โค U = B< S           โฆ(i)
B โค X                        โฆ(ii)
Combining (i) and (ii), we get
R โค U = B โค X
Thus, R โค X or X โฅ R is true.
It means either X> R or X = R is true.
Hence either conclusion I or II is true.

4). Given statements:
C> U โค S< T = O> D โฅ Y               โฆ(i)
Z = O โค P                                          โฆ(ii)
Combining (i) and (ii) we get
C> U โค S< T = O โค P
Thus, S< P is true. Hence conclusion II is true.
Again. C> U โค S< T = O = Z> D
We canโt compare U and D. Hence I (U> D) is not true

5). Given statements:
C> U โค S< T = O> D โฅ Y               โฆ(i)
Z = O โค P                                          โฆ(ii)
Combining (i) and (ii) we get
C> U โค S< T = O = Z> D โฅ Y
Thus, Z> Y is true. Hence I is true. Again we canโt compare C and O. Hence II (C< O) is not true.

6). Given statements:
P = N โฅ Q> R            .. (i)
K< T = R                  ..(ii)
Combining both statements, we get
K< T = R< Q โค N = P
Thus, K< p or P> K is true. Hence conclusion I is true.
Again, T< Q or Q> T (conclusion II) is true.
Hence both conclusions are true

7). Given statements:
G< W = S โค H                       โฆ(i)
Z โฅ B = G                              โฆ(ii)
Combining both statements, we get
Z โฅ B = G< W = S โค H
Thus, we canโt compare W and Z. Hence I (W< Z) is not true.
Again, B< H or H> B is true. Hence conclusion II is true

8). Given statement:
C โฅ D โฅ N = J< K โค R
Thus, N< R or R> N is true.
Again, we canโt compare D and K. Hence II D โฅ K is not true. Hence only I is true

9). Given statements:
E โฅ G> H< I              โฆ(i)
K = M โฅ N< E           โฆ(ii)
Combining both statements, we get
K = M โฅ N< E โฅ G> H< I
Thus, we canโt compare M and G.
Hence I (M = G) is not true.
Again, we canโt compare N and H. Hence II (N โฅ H) is not true
Hence both are not true

10). Given statements:
L โค M> N โฅ R                        โฆ(i)
G> S= T โฅ R                        โฆ(ii)
Combining both statements we get
G> S= T โฅ R โค N< M โฅ L
Thus, T โค N is not true.
Again, G> R is true. Hence only II is true

For More Reasoning Questions

/ 5. Reviews

Online Mock Tests 2019: